2020
DOI: 10.1037/amp0000636
|View full text |Cite
|
Sign up to set email alerts
|

Patient race and opioid misuse history influence provider risk perceptions for future opioid-related problems.

Abstract: In response to the dual public health crises of chronic pain and opioid use, providers have become more vigilant about assessing patients for risk of opioid-related problems. Little is known about how providers are making these risk assessments. Given previous studies indicating that Black patients are at increased risk for suboptimal pain care, which may be related to stereotypes about drug abuse, the current study examined how patient race and previous opioid misuse behaviors impact providers’ risk assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 57 publications
2
24
0
Order By: Relevance
“…Providers should also be mindful of implicit bias risks when assessing and treating pain. Multiple analyses have found that lower amounts of analgesics are routinely prescribed to Black and other patients of color despite higher degrees of self-reported pain, and that race influences prescriber perceptions of risk for opioid misuse [ 362 , 363 , 364 ].…”
Section: Pain Management and Opioid Stewardship Across The Periopementioning
confidence: 99%
“…Providers should also be mindful of implicit bias risks when assessing and treating pain. Multiple analyses have found that lower amounts of analgesics are routinely prescribed to Black and other patients of color despite higher degrees of self-reported pain, and that race influences prescriber perceptions of risk for opioid misuse [ 362 , 363 , 364 ].…”
Section: Pain Management and Opioid Stewardship Across The Periopementioning
confidence: 99%
“…There are several possible explanations for why providers underestimate and undertreat Black patients’ pain, including incorrect provider beliefs about Black patients’ nerve endings and skin, 6 or suspicion that Black patients are more likely to abuse opioids than White patients. 24, 25 It is also possible that these results do not indicate bias, but instead represent racial trends in opioid abuse, since during this time period the opioid crisis disproportionately affected White Americans. 26 Both of these factors are likely to be intertwined in practice.…”
Section: Discussionmentioning
confidence: 95%
“…This theory is consistent with the results of previous studies, which have found that clinicians make different pain management decisions in response to identical patient-level information when treating Black vs White patients. 18 , 32 …”
Section: Discussionmentioning
confidence: 99%